2022
DOI: 10.21203/rs.3.rs-2077742/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quality of Life Changes in Taiwanese Dentofacial Deformity Patients Undergoing Orthognathic Surgery

Abstract: Objectives The evaluation of orthognathic surgery (OgS) is shifting towards a coherent approach for patient care that balances objective clinician-defined measures with patient-centred outcome assessments, including health-related quality of life (QoL). This aim of this study adds to the pool of literature in East Asian subjects by studying the longitudinal QoL changes in Taiwanese patients with dentofacial deformities (DFD) undergoing OgS, using two standardized questionnaires at three different treatment st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The results of the selected studies, although diverse in nature, mostly focus on analyzing the importance of the SFA approach in mitigating various dentofacial deformities. For example, the cohort study by Ng et al [1] has been found to be largely related to the "skeletal class III" patients. In their sample, 84.4% of the patients were found to benefit from surgery.…”
Section: Synthesis Of the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the selected studies, although diverse in nature, mostly focus on analyzing the importance of the SFA approach in mitigating various dentofacial deformities. For example, the cohort study by Ng et al [1] has been found to be largely related to the "skeletal class III" patients. In their sample, 84.4% of the patients were found to benefit from surgery.…”
Section: Synthesis Of the Resultsmentioning
confidence: 99%
“…Quality of life changes in Taiwanese dentofacial deformity patients undergoing orthognathic surgery Ng et al 2022 [1] 3…”
Section: Outcomes (Out Of 5)mentioning
confidence: 99%
See 1 more Smart Citation